Parâmetros inflamatórios, oxidativos e morfometria intestinal de frangos de corte alimentados com óleo essencial de cúrcuma em conforto e estresse térmico - Macário, Maíse dos Santos (2023)
In poultry, the effects of high temperatures are mainly responsible for affecting the entire production system due to heat stress. Furthermore, modern broilers are particularly sensitive to hot temperatures due to their rapid growth rates (accelerated metabolism), which leaves the birds constantly in a state of latent oxidation and inflammation leading to oxidative stress. Oxidative stress makes it easier for the bird to suffer the consequences of heat stress more quickly, therefore, it is necessary to search for effective alternatives to repair the negative effects of this imbalance and improve the productive performance of the animals. Turmeric essential oil is a promising alternative, since it comes from a herbaceous species of the Zingiberaceae family, whose antioxidant, anti-inflammatory, anti-bacterial, anti-apoptosis and anticancer attributes have been described for some years. Thus, the objectives of this study were: (1) to discuss the potential of turmeric essential oil as an attenuator of the effects of heat and oxidative stress in broilers; (2) to evaluate the response in performance, organ weight, intestinal morphometry, heterophil-lymphocyte ratio and gene expression in broiler chickens from 21 to 42 days old under comfort (24ºC) and chronic cyclic heat stress (33ºC to 35ºC from 8 am at 6 pm and 21°C to 26°C from 6 pm to 8 am), fed with different levels of turmeric essential oil. In article 1, the potential of turmeric essential oil to improve the negative effect of heat stress on broiler chickens was described, in a review format, showing the results obtained so far with the use of the essential oil and establishing hypotheses based on the results obtained in the use of powdered turmeric extract. For article 2, a total of 320 male cobb 500 broilers aged 21 to 42 days were evaluated. Treatments consisted of a negative control diet without essential oil (SOE) and three diets with low (OE-1: 100mg/kg), medium (OE-2: 200mg/kg) and high (OE-3: 300mg/kg) kg) of inclusion of turmeric essential oil in comfort and stress environments. Under stress, at concentrations of 100 and 200 mg/kg of turmeric essential oil inclusion, there was an improvement in live weight, feed conversion, breast yield and relative weight of the liver of birds. A reduction in villus width and a higher villus:crypt ratio were also observed at these inclusion levels in the heat stress environment, as well as a reduction in the heterophil-lymphocyte ratio in the blood and an effect on the expression of the HSP70, OCLN and SREBP-1 genes. These findings support the hypothesis that the use of turmeric essential oil is efficient in reestablishing or improving intestinal integrity, inflammatory aspects and, consequently, the performance of broiler chickens under chronic heat stress, with the recommendation of 100 mg/kg on the diet.